A Reconstruction of Subtropical Western North Pacific SST Variability Back to 1578, Based on a Porites Coral Sr/Ca Record from the Northern Ryukyus, Japan. (7th December 2017) - Kawakubo, Y.; Alibert, C.; Yokoyama, Y.
Abstract: We present a seasonal reconstruction of sea surface temperature (SST) from 1578 to 2008, based on a Porites coral Sr/Ca record from the northern Ryukyus, within the Kuroshio southern recirculation gyre. Interannual SST anomalies are generally 0.5°C, making Sr/Ca‐derived SST reconstructions a challenging task. Replicate measurements along adjacent coral growth axes, enabled by the laser ablation inductively coupled plasma mass spectrometry technique used here, give evidence of rather large uncertainties. Nonetheless, derived winter SST anomalies are significantly correlated with the Western Pacific atmospheric pattern which has a dominant influence on winter temperature in East Asia. Annual mean SSTs show interdecadal variations, notably cold intervals between 1670 and 1700 during the Maunder Minimum (MM) and between 1766 and 1788 characterized by a negative phase of the North Atlantic Oscillation. Cold summers in 1783 and 1784 coincide with the long‐lasting Laki eruption that had a profound impact on the Northern Hemisphere climate, including the severe "Tenmei" famine in Japan. The decades between 1855 and 1900 are significantly cooler than the first half of the twentieth century, while those between 1700 and 1765, following the MM, are warmer than average. SST variability in the Ryukyus is only marginally influenced by the Pacific Decadal Oscillation, so that external forcing remains the main driver of low‐frequency temperature changes. However, the close connection between the Kuroshio extension (KE) and its recirculation gyre suggests that decadal SST anomalies associated with the KE front also impact the Ryukyus, and there is a possible additional role for feedback of the Kuroshio‐Oyashio variability to the large‐scale atmosphere at decadal timescale. Key Points: Coral SST reconstruction (1578–2009) for subtropical western North Pacific Proxy for Western Pacific teleconnection pattern Record of "Little Ice Age" in South Japan